Prioridad del traije y tiempo de espera en la atención de pacientes de emergencia del Hospital Regional de Loreto, Iquitos 2020 - Sánchez Arbaiza, Neri Nabela (2022)
This research was aimed at determining the relationship between the priority levels of the suit and the waiting time in the care of patients in the emergency service of the Regional Hospital of Loreto, Iquitos 2020. it is a descriptive, correlational, cross-sectional, prospective investigation, applied to 138 patients the triage priority level assessment form and emergency waiting time. The results show that, of the 70.3% who had adequate waiting, 36.2% qualified with triage III priority, finding a significant statistical relationship (p=0.001). The average waiting time of patients with priority I, is less than the waiting of patients with priority III and IV (p<0.05). The study concludes that the majority of patients who attend the emergency service of the Regional Hospital of Loreto qualify as priority III and the waiting time aim of determining the relationship between triage priority levels and waiting time is 70.3%.